A study of high fat milk replacers and high fat postweaning diets in the rearing of young Friesland bull-calves - Ford, D. P (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- Stellenbosch University, 1977.